The paperboy [videorecording (DVD)] - Daniels, Lee, 1959-; McConaughey, Matthew, 1969-; Efron, Zac; Kidman, Nicole, 1967-; Oyelowo, David (Echo Bridge Acquisition Corp. LLC, 2018)
It takes audiences deep into the backwaters of steamy 1960s South Florida, as investigative reporter Ward Jansen and his partner Yardley Acheman chase a sensational, career-making story. With the help of Ward's younger brother Jack and sultry death-row groupie Charlotte Bless, the pair tries to prove violent swamp-dweller Hillary Van Wetter was framed for the murder of a corrupt local sheriff.